Determining the long-term changes in biodiversity and provisioning services along a transect from Central Europe to the Mediterranean. - Colombaroli, Daniele; Tinner, Willy (Holocene, 2013)
Climate, land use and fire are strong determinants of plant diversity, potentially resulting in local extinctions, including rare endemic and economically valuable species. While climate and land use are decisive for vegetation composition and thus the species pool, fire disturbance can lead to landscape fragmentation, affecting the provisioning of important ecosystem services such as timber and raw natural resources. We use multi-proxy palaeoecological data with high taxonomic and temporal resolution across an environmental gradient to assess the long-term impact of major climate shifts, land use and fire disturbance on past vegetation openness and plant diversity (evenness and richness). Evenness of taxa is inferred by calculating the probability of interspecific encounter (PIE) of pollen and spores and species richness by palynological richness (PRI). To account for evenness distortions of PRI, we developed a new palaeodiversity measure, which is evenness-detrended palynological richness (DE-PRI). Reconstructed species richness increases from north to south regardless of time, mirroring the biodiversity increase across the gradient from temperate deciduous to subtropical evergreen vegetation. Climatic changes after the end of the last ice age contributed to biodiversity dynamics, usually by promoting species richness and evenness in response to warming. The data reveal that the promotion of diverse open-land ecosystems increased when human disturbance became determinant, while forests became less diverse. Our results imply that the today’s biodiversity has been shaped by anthropogenic forcing over the millennia. Future management strategies aiming at a successful conservation of biodiversity should therefore consider the millennia-lasting role of anthropogenic fire and human activities. [ABSTRACT FROM AUTHOR]
The following values have no corresponding Zotero field: publisher: Sage Publications, Ltd.
Keywords: climate; ecosystem services; evenness-detrended palynological richness; fire; land use; plant diversity

Isoscapes of tree-ring carbon-13 perform like meteorological networks in predicting regional precipitation patterns - del Castillo, Jorge; Aguilera, Monica; Voltas, Jordi; Pedro Ferrio, Juan (JOURNAL OF GEOPHYSICAL RESEARCH-BIOGEOSCIENCES, 2013)
Stable isotopes in tree rings provide climatic information with annual resolution dating back for centuries or even millennia. However, deriving spatially explicit climate models from isotope networks remains challenging. Here we propose a methodology to model regional precipitation from carbon isotope discrimination (Delta C-13) in tree rings by (1) building regional spatial models of Delta C-13 (isoscapes) and (2) deriving precipitation maps from Delta C-13-isoscapes, taking advantage of the response of Delta C-13 to precipitation in seasonally dry climates. As a case study, we modeled the spatial distribution of mean annual precipitation (MAP) in the northeastern Iberian Peninsula, a region with complex topography and climate (MAP = 303-1086 mm). We compiled wood Delta C-13 data for two Mediterranean species that exhibit complementary responses to seasonal precipitation (Pinus halepensis Mill., N = 38; Quercus ilex L.; N= 44; pooling period: 1975-2008). By combining multiple regression and geostatistical interpolation, we generated one Delta C-13-isoscape for each species. A spatial model of MAP was then built as the sum of two complementary maps of seasonal precipitation, each one derived from the corresponding Delta C-13-isoscape (September-November from Q. ilex; December-August from P. halepensis). Our approach showed a predictive power for MAP (RMSE = 84 mm) nearly identical to that obtained by interpolating data directly from a similarly dense network of meteorological stations (RMSE = 80-83 mm, N= 65), being only outperformed when using a much denser meteorological network (RMSE = 56-57 mm, N = 340). This method offers new avenues for modeling spatial variability of past precipitation, exploiting the large amount of information currently available from tree-ring networks.
CitationCitationThe following values have no corresponding Zotero field: pub-location: 2000 FLORIDA AVE NW, WASHINGTON, DC 20009 USA publisher: AMER GEOPHYSICAL UNION
Keywords: ARCHAEOBOTANICAL REMAINS; ATMOSPHERIC CO2; CARBON-ISOTOPE DISCRIMINATION; climate; DELTA-C-13; PINUS-HALEPENSIS; RAINFALL; STABLE-ISOTOPES; Temperature

Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Sarcosaprophagous Diptera assemblages in natural habitats in central Spain: spatial and seasonal changes in composition - MARTÍN-VEGA, D; Baz, A (Medical and Veterinary Entomology, 2012)
The composition and spatial distribution of sarcosaprophagous Diptera assemblages were studied using carrion-baited traps along a bioclimatic gradient of natural habitats in central Spain throughout the different seasons during 1 year. Calliphoridae and Muscidae were the most abundant families, accounting for, respectively, 41.9% and 35.1% of all Diptera specimens collected. Other abundant families were Heleomyzidae (8.4%), Sarcophagidae (6.9%) and Piophilidae (5.1%). Fly assemblage compositions differed among bioclimatic levels, with Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) being the dominant species in mesomediterranean habitats, Muscina levida (Harris) (Diptera: Muscidae) the dominant species in supramediterranean habitats, and Prochyliza nigrimana (Meigen) (Diptera: Piophilidae) the dominant species in oromediterranean habitats. Differences in assemblage composition were also found among seasons. Thermophobic species such as Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) and some species of Heleomyzidae were well represented during autumn, winter and spring in the three bioclimatic levels sampled. By contrast, thermophilic species such as Ch. albiceps and Lucilia sericata (Meigen) (Diptera: Calliphoridae) and most Muscidae and Sarcophagidae species were more abundant during summer and in mesomediterranean habitats located at lower elevations. Knowledge of the preferences of some species for certain habitats may be of ecological and forensic value and may establish a starting point for further research.
Keywords: Animals; Biota; climate; Diptera; Diptera: classification; Diptera: physiology; Ecosystem; Forensic entomology; habitat association; sarcosaprophagous Diptera; Seasons; Spain

Vegetation, fire, climate and human disturbance history in the southwestern Mediterranean area during the late Holocene - Jiménez-Moreno, Gonzalo; García-Alix, Antonio; Hernández-Corbalán, María Dolores; Anderson, R. Scott; Delgado-Huertas, Antonio (Quaternary Research, 2012)
Detailed pollen, charcoal, isotope and magnetic susceptibility data from an alpine lake sediment core from Sierra Nevada, southern Spain record changes in vegetation, ﬁre history and lake sedimentation since ca. 4100 cal yr BP. The proxies studied record an arid period from ca. 3800 to 3100 cal yr BP characterized by more xerophytic vegetation and lower lake levels. A humid period is recorded between ca. 3100 and 1850 cal yr BP, which occurred in two steps: (1) an increase in evergreen Quercus between 3100 and 2500 cal yr BP, indicating milder conditions than previously and (2) an increase in deciduous Quercus and higher lake levels, between ca. 2500 and 1850 cal yr BP, indicating a further increase in humidity and reduction in seasonal contrast. Humid maxima occurred during the Roman Humid Period, previously identiﬁed in other studies in the Mediterranean region. Intensiﬁed ﬁre activity at this time could be related to an increase in fuel load and/or in human disturbance. An arid period subsequently occurred between 1850 and 650 cal yr BP, though a decrease in Quercus and an increase in xerophytes. The alternation of persistent North Atlantic Oscillation modes probably played an important role in controlling these humid–arid cycles
The following values have no corresponding Zotero field: publisher: University of Washington
Keywords: climate; Fire history; Late Holocene; Roman Humid Period; Sierra Nevada; southern Spain

Equilibrium of vegetation and climate at the European rear edge. A reference for climate change planning in mountainous Mediterranean regions. - Ruiz-Labourdette, Diego; Martínez, Felipe; Martín-López, Berta; Montes, Carlos; Pineda, Francisco D (International journal of biometeorology, 2011)
Mediterranean mountains harbour some of Europe's highest floristic richness. This is accounted for largely by the mesoclimatic variety in these areas, along with the co-occurrence of a small area of Eurosiberian, Boreal and Mediterranean species, and those of Tertiary Subtropical origin. Throughout the twenty-first century, we are likely to witness a climate change-related modification of the biogeographic scenario in these mountains, and there is therefore a need for accurate climate regionalisations to serve as a reference of the abundance and distribution of species and communities, particularly those of a relictic nature. This paper presents an objective mapping method focussing on climate regions in a mountain range. The procedure was tested in the Cordillera Central Mountains of the Iberian Peninsula, in the western Mediterranean, one of the ranges occupying the largest area of the Mediterranean Basin. This regionalisation is based upon multivariate analyses and upon detailed cartography employing 27 climatic variables. We used spatial interpolation of data based on geographic information. We detected high climatic diversity in the mountain range studied. We identified 13 climatic regions, all of which form a varying mosaic throughout the annual temperature and rainfall cycle. This heterogeneity results from two geographically opposed gradients. The first one is the Mediterranean-Euro-Siberian variation of the mountain range. The second gradient involves the degree of oceanicity, which is negatively related to distance from the Atlantic Ocean. The existing correlation between the climatic regions detected and the flora existing therein enables the results to be situated within the projected trends of global warming, and their biogeographic and ecological consequences to be analysed.
Keywords: climate; Cordillera Central Mountains of the Iberian Penins; Geographic factors; Global warming; Mediterranean flora; Multivariate regression with climatic data

Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact - Jalut, Guy; Dedoubat, Jean Jacques; Fontugne, Michel; Otto, Thierry (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.
Keywords: climate; climatic changes; Holocene; Mediterranean area; pollen data; vegetation dynamics (voyant)

Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact - Jalut, Guy; Dedoubat, Jean Jacques; Fontugne, Michel; Otto, Thierry (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.
Keywords: climate; climatic changes; Holocene; Mediterranean area; pollen data; vegetation dynamics (voyant)

Variation in cold hardiness and carbohydrate concentration from dormancy induction to bud burst among provenances of three European oak species - Morin, Xavier; Améglio, Thierry; Ahas, Rein; Kurz-Besson, Cathy; Lanta, Vojtěch; Lebourgeois, François; Miglietta, Franco; Chuine, Isabelle (Tree Physiology, 2007)
Although cold hardiness is known to be a major determinant of tree species distribution, its dynamics and the factors that regulate it remain poorly understood. Variation in cold hardiness and carbohydrate concentration, from dormancy induction until bud burst, were investigated in populations of two deciduous (Quercus robur L. and Quercus pubescens Willd.) and one evergreen (Quercus ilex L.) European oak. Mean cold hardiness values in January were –56, –45 and –27 °C for Q. robur, Q. pubescens and Q. ilex, respectively. Soluble carbohydrate concentrations were closely related to instantaneous cold hardiness, estimated by the electrolyte leakage method, whereas total carbohydrate concentration was related to maximum cold hardiness. Both cold hardiness and carbohydrate concentration showed a close linear relationship with temperatures at the location of the sampled population. Our results show that temporal variation in both the inter- and intraspecific cold hardiness in European oaks can be related to variations in the concentrations of soluble carbohydrates and that these relationships appear to be driven by temperature.
10.1093/treephys/27.6.81710.1093/treephys/27.6.817
Keywords: adult individuals; climate; distribution; frost dam- age; natural populations; Phenology; Quercus ilex; Quercus pubescens; Quercus robur

Variation in cold hardiness and carbohydrate concentration from dormancy induction to bud burst among provenances of three European oak species - Morin, Xavier; Améglio, Thierry; Ahas, Rein; Kurz-Besson, Cathy; Lanta, Vojtěch; Lebourgeois, François; Miglietta, Franco; Chuine, Isabelle (Tree Physiology, 2007)
Although cold hardiness is known to be a major determinant of tree species distribution, its dynamics and the factors that regulate it remain poorly understood. Variation in cold hardiness and carbohydrate concentration, from dormancy induction until bud burst, were investigated in populations of two deciduous (Quercus robur L. and Quercus pubescens Willd.) and one evergreen (Quercus ilex L.) European oak. Mean cold hardiness values in January were –56, –45 and –27 °C for Q. robur, Q. pubescens and Q. ilex, respectively. Soluble carbohydrate concentrations were closely related to instantaneous cold hardiness, estimated by the electrolyte leakage method, whereas total carbohydrate concentration was related to maximum cold hardiness. Both cold hardiness and carbohydrate concentration showed a close linear relationship with temperatures at the location of the sampled population. Our results show that temporal variation in both the inter- and intraspecific cold hardiness in European oaks can be related to variations in the concentrations of soluble carbohydrates and that these relationships appear to be driven by temperature.
10.1093/treephys/27.6.817
Keywords: adult individuals; climate; distribution; frost dam- age; natural populations; Phenology; Quercus ilex; Quercus pubescens; Quercus robur

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G. (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
The following values have no corresponding Zotero field: accession-num: 15997399
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather

Climatic factors and establishment of Quercus ilex-communities in Trieste Province (NE Italy) - Codogno, M; Furlanetto, A (Annali di Botanica, 2004)
In the coastal area called "Cernizza" (near Duino. ca 15 km NW from Trieste), at an altitude between 0 and 40 m. is located a wood vegetation complex characterized by Quercus ilex and Carpinus orientalis. The bedrocks of this site is carbonatic. This wood vegetation does not occur in other sites or the Trieste province, where deciduous oak woods (Q. pubescells, Q. petraea s.1.) are dominant both on arenaceus and on carbonatic rocks. Other Quercus ilex communities are occurring only as scrubs on the calcareous coastal cliffs characterized by primitive lithosoils. In order to detect if this wood community might be an expression of the c1imate dominating this particular zone, some Duino's c1imatic data, relative lo a record period of 9 years. have been compared with the Trieste's ones. The analysed parameters were the following: air temperature. rainfall, evaporation. wind speed and relative humidity. From the comparison of these paramenters it emerged that the Duino's climate is more humid than the Trieste's one. Only in springtime Duino is less rainy than Trieste according lo the analysis of the monthly mean values of precipitation. From the ecophysiological point of view, a study of the seasonal changes of the root hydraulic conductance in some forest trees (Nardini el al .. 1998) has pointed out the superiority of Quercus ilex compared to Quercus pubescens, as regards the competitive ability of the seedlings during the spring. For this reason, the smaller spring rainfall could explain the occurrence of Quercus ilex stands not only in the neighbourhood of Duino but also at the beginning of the large valleys characterized by S•N direction in the South Eastern Alps.
Keywords: climate; Holm oak; plant ecology; Quercus ilex; Trieste province; Vegetation

Climatic factors and establishment of Quercus ilex-communities in Trieste Province (NE Italy) - Codogno, M.; Furlanetto, A. (Annali di Botanica, 2004)
In the coastal area called "Cernizza" (near Duino. ca 15 km NW from Trieste), at an altitude between 0 and 40 m. is located a wood vegetation complex characterized by Quercus ilex and Carpinus orientalis. The bedrocks of this site is carbonatic. This wood vegetation does not occur in other sites or the Trieste province, where deciduous oak woods (Q. pubescells, Q. petraea s.1.) are dominant both on arenaceus and on carbonatic rocks. Other Quercus ilex communities are occurring only as scrubs on the calcareous coastal cliffs characterized by primitive lithosoils. In order to detect if this wood community might be an expression of the c1imate dominating this particular zone, some Duino's c1imatic data, relative lo a record period of 9 years. have been compared with the Trieste's ones. The analysed parameters were the following: air temperature. rainfall, evaporation. wind speed and relative humidity. From the comparison of these paramenters it emerged that the Duino's climate is more humid than the Trieste's one. Only in springtime Duino is less rainy than Trieste according lo the analysis of the monthly mean values of precipitation. From the ecophysiological point of view, a study of the seasonal changes of the root hydraulic conductance in some forest trees (Nardini el al .. 1998) has pointed out the superiority of Quercus ilex compared to Quercus pubescens, as regards the competitive ability of the seedlings during the spring. For this reason, the smaller spring rainfall could explain the occurrence of Quercus ilex stands not only in the neighbourhood of Duino but also at the beginning of the large valleys characterized by S•N direction in the South Eastern Alps.
Keywords: climate; Holm oak; plant ecology; Quercus ilex; Trieste province; Vegetation

Effects of a severe drought on Quercus ilex radial growth and xylem anatomy - Gil-Pelegrín, Eustaquio; Corcuera, Leyre; Camarero, Jesús Julio (Trees - Structure and Function, 2004)
We assessed the response of Quercus ilex subsp. ballota to the severe summer drought recorded in 1994 in NE Spain through the study of changes in radial growth and wood anatomy. We selected a coppice stand in the Iberian Peninsula, which is characterized by a Mediterranean climate under continental influence. We measured internode length, tree-ring width, mean and maximum vessel diameter, and vessel density for 1981– 1997. The annual predicted hydraulic conductance (Kh) was calculated following Hagen-Poisseuille’s law. We compared the tree-ring width, vessel diameter and Kh of Q. ilex subsp. ballota and co-existing ring-porous oaks (Q. faginea, Q. pyrenaica) for a dry summer (1994) and a wet summer (1997). To evaluate the drought-resistance of xylem for Q. ilex subsp. ballota (dominant under continental conditions) and Q. ilex subsp. ilex (dominant in mild areas) we determined vulnerability curves. Dimensionless indices of internode length, tree-ring width, and vessel density were compared with climatic data (monthly total precipitation and mean temperature) using correlation analyses. Internode length, tree-ring width, Kh, and mean and maximum vessel diameter declined in 1994. According to vulnerability curves, Q. ilex subsp. ballota showed a greater drought resistance than Q. ilex subsp. ilex. During the year of growth, we found a positive influence of January and June–August precipitation on the internode length, tree-ring width, and vessel density. The response of Q. ilex subsp. ballota radial-growth to summer drought was comparable to that of Q. faginea latewood. Overall, growth and wood anatomy of Q. ilex subsp. ballota showed a plastic response to drought.
Keywords: cavitation; climate; Dendroecology; vulnerability curve; Xylem

An examination of the interaction between climate, soil and leaf area index in a Quercus ilex ecosystem - Hoff, Corine; Rambal, Serge (Ann. For. Sci., 2003)
In Mediterranean-type ecosystems, water availability is one of the most significant variables that regulates whole plant leaf area. An equilibrium should exist between climate, soil and leaf area in such water-limited conditions. The aim of this study was to identify the relations between leaf area index (LAI), environment (climate, soil) and fluxes (water, carbon) in Mediterranean evergreen oak (Quercus ilex L.) ecosystems. To achieve this objective, 50-years simulations were performed using the FOREST-BGC model by varying LAI for a reference site and for different climates and soil water holding capacities (SWC). Transpiration, drought stress, net photosynthesis and canopy water use efficiency (WUE) were examined on a yearly basis for the last ten years of the simulation. Similar to other findings, our results show that LAI depends on site water availability, including both climate (precipitation, potential evapotranspiration) and soil factors (e.g. water storage capacity). Low SWC limit the development of the ecosystem. On high SWC soils, development is mainly limited by the climate. When LAI increases under constant SWC and climate conditions, the decrease in annual transpiration per unit of LAI is accompanied by an increase in drought stress. Equilibrium LAI maximizes carbon assimilation. For the reference site, the equilibrium LAI is close to the observed value, 3.25. The corresponding transpiration, assimilation and WUE are 375 mm, 1251 g C m -2 and 3.1 mmol CO 2 mol -1 H 2O, respectively. For the different sites, there is an hyperbolic decline of WUE with increasing SWC. This implies that production efficiency per unit leaf area is higher in most water-limited environments. Our study shows that a model such as FOREST-BGC allows inter-relations between water balance, carbon balance and drought stress to be taken into account to better understand ecosystem LAI.
Keywords: climate; evergreen oak; hydrological equilibrium; leaf area index; mediterranean-type ecosystem; Quercus ilex L.; soil factor; Water availability

Influencia del clima en el crecimiento longitudinal y radial de Q. ilex ssp. ballota L. y Q. faginea Lam. EN EL SISTEMA IBERICO ARAGONES - Corcuera, L.; Camarero, J. J.; GIL-PELEGRÍN, E. (III Congreso Forestal Español, 2001)
Climate influence (precipitation and temperature) on primary growth (annual growth length) and secondary growth (ring width and ring surface) of Quercus ilex ssp. ballota L. (evergreen and diffuse-porous species) and Q. faginea Lam. (decidious and ring-porous species) is studied. Samples were taken from a coppice in Sierra de Santa Cruz, Cubel, Zaragoza. Both species show lesser longitudinal and radial growth in drought years. A positive and significant relationship between precipitation and secondary growth and a negative and significant relationship between high summer temperatures and secondary growth were observed. Primary and secondary growth in 1993 and previous years mirror foliage desiccation of Q. ilex in 1993.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español issue: 1 pub-location: Granada
Keywords: climate; primary growth; Q. faginea; Q. ilex ssp. ballota; secondary growth

Influencia del clima en el crecimiento longitudinal y radial de Q. ilex ssp. ballota L. y Q. faginea Lam. EN EL SISTEMA IBERICO ARAGONES - Corcuera, L; CAMARERO, J J; Gil-Pelegrín, E (III Congreso Forestal Español, 2001)
Climate influence (precipitation and temperature) on primary growth (annual growth length) and secondary growth (ring width and ring surface) of Quercus ilex ssp. ballota L. (evergreen and diffuse-porous species) and Q. faginea Lam. (decidious and ring-porous species) is studied. Samples were taken from a coppice in Sierra de Santa Cruz, Cubel, Zaragoza. Both species show lesser longitudinal and radial growth in drought years. A positive and significant relationship between precipitation and secondary growth and a negative and significant relationship between high summer temperatures and secondary growth were observed. Primary and secondary growth in 1993 and previous years mirror foliage desiccation of Q. ilex in 1993.
Keywords: climate; primary growth; Q. faginea; Q. ilex ssp. ballota; secondary growth

Climatic classification and ordination of the Spanish Sistema Central: relationships with potential vegetation - Gavilán, R G; Fernández-González, F; Blasi, C (Plant Ecology, 1998)
Monthly precipitation and monthly mean temperature records from 255 meteorological stations in Central Spain (Spanish Sistema Central) were analyzed by cluster and principal component analyses. Classiﬁcation separated 14 groups according to altitude, geographical distribution, as well as the combination of rainfall and temperature. The ﬁrst cluster emerged as signiﬁcantly higher and colder than the second. Then, two ordinations were carried out: one for the 14 groups extracted from the classiﬁcation and a second for the total station pool. The second ordination was compared with potential natural vegetation data taken around each station. The ﬁrst ordination summarized the principal climatic characteristics of the Spanish Sistema Central: its behaviour is that of a typical Mediterranean mountainous territory combining summer aridity and variation of temperature with altitude and the inﬂuence of winter winds. The ordination of all stations reﬂected a thermal, rainfall and summer aridity gradient. Meteorological stations situated at the highest altitude or with highest precipitation records characterized by scrub communities or pine woods and Quercus pyrenaica forests, appeared well-separated along the ﬁrst two axes. Only the most thermophilous Q. rotundifolia associations could be clearly separated. The fourth axis was useful in clarifying some vegetation overlap of deciduous and sclerophyllous forests, along an east-west summer aridity gradient.
Keywords: climate; cluster analysis; potential vegetation; Precipitation; Principal component analysis; Spain; Temperature

Holocene climatic change in Morocco: a quantitative reconstruction from pollen data - Cheddadi, R; Lamb, H F; Guiot, J; van der Kaars, S (Climate Dynamics, 1998)
Annual precipitation, July and January tem- peratures were reconstructed from a continuous Holo- cene pollen sequence from the Middle Atlas, Morocco, using the best modern analogues method. The recon- structions show a clear difference between the early and late Holocene: from &10 ka to &6.5 ka the climate was drier and warmer than during the period since 6.5 ka. The average value of annual precipitation was &870mm until 6.5 ka, then rose to &940 mm. Be- tween 10 ka and 6.5 ka January and July temperatures were about 4 °C higher than the present. Both temper- atures show a marked decrease between 7 ka and 6 ka. After 6.5 ka July and January temperatures fluctuated between 21 and 23 °C, and 2.5 and 5 °C respectively. January temperatures show a period of intermediate values (&3.5 °C) between 4 ka and 5.5 ka. The recon- structed climate values generally match palaeolim- nological data from the same core, which show five intervals of low lake level during the Holocene. They are also consistent with regional-scale COHMAP simulated palaeoclimate that shows contrasting pat- terns of rainfall variation between the northwester- nmost part of Africa and the intertropical band
APS
Keywords: climate; Holocene; Morocco; paleoclimate; pollen

Holocene climatic change in Morocco: a quantitative reconstruction from pollen data - Cheddadi, R.; Lamb, H. F.; Guiot, J.; van der Kaars, S. (Climate Dynamics, 1998)
Annual precipitation, July and January tem- peratures were reconstructed from a continuous Holo- cene pollen sequence from the Middle Atlas, Morocco, using the best modern analogues method. The recon- structions show a clear difference between the early and late Holocene: from &10 ka to &6.5 ka the climate was drier and warmer than during the period since 6.5 ka. The average value of annual precipitation was &870mm until 6.5 ka, then rose to &940 mm. Be- tween 10 ka and 6.5 ka January and July temperatures were about 4 °C higher than the present. Both temper- atures show a marked decrease between 7 ka and 6 ka. After 6.5 ka July and January temperatures fluctuated between 21 and 23 °C, and 2.5 and 5 °C respectively. January temperatures show a period of intermediate values (&3.5 °C) between 4 ka and 5.5 ka. The recon- structed climate values generally match palaeolim- nological data from the same core, which show five intervals of low lake level during the Holocene. They are also consistent with regional-scale COHMAP simulated palaeoclimate that shows contrasting pat- terns of rainfall variation between the northwester- nmost part of Africa and the intertropical band
APSAPS
Keywords: climate; Holocene; Morocco; paleoclimate; pollen

Climatic discrimination of Mediterranean broad-leaved sclerophyllous and deciduous forests in central Spain - Gavilán, Rosario; Fernández-González, Federico (Journal of Vegetation Science, 1997)
Abstract. Climatic differences between three types of deciduous (Quercus pyrenaica) and three types of sclerophyllous (Quercus rotundifolia) Mediterranean forests in the Spanish Sistema Central were analyzed by means of Canonical Discriminant Analysis and Jancey's Discriminant Analysis, applied in successive steps to data from 252 meteorological stations. Climatic data included temperature and precipitation records as well as bioclimatic indices. Discriminant analysis was applied to broad-leaved sclerophyllous and deciduous forest communities sampled at each meteorological station using phytosociological methods. Annual and seasonal (summer, spring) water availability are the most important factor controlling the distribution of the two physiognomic forest types; southwestern associations of Quercus pyrenaica and Q. rotundifolia differ from their colder homologues by annual and monthly temperatures; western associations were separated from eastern ones in terms of annual and seasonal precipitation gradients. Discriminant analysis was a good technique to explore climatic gradients not shown by other general ordination or classification methods.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Bioclimatic indices; climate; Continentality; Discriminant analysis; Summer aridity; Water availability

Climatic discrimination of Mediterranean broad-leaved sclerophyllous and deciduous forests in central Spain - Gavilán, Rosario; Fernández-González, Federico (Journal of Vegetation Science, 1997)
Abstract. Climatic differences between three types of deciduous (Quercus pyrenaica) and three types of sclerophyllous (Quercus rotundifolia) Mediterranean forests in the Spanish Sistema Central were analyzed by means of Canonical Discriminant Analysis and Jancey's Discriminant Analysis, applied in successive steps to data from 252 meteorological stations. Climatic data included temperature and precipitation records as well as bioclimatic indices. Discriminant analysis was applied to broad-leaved sclerophyllous and deciduous forest communities sampled at each meteorological station using phytosociological methods. Annual and seasonal (summer, spring) water availability are the most important factor controlling the distribution of the two physiognomic forest types; southwestern associations of Quercus pyrenaica and Q. rotundifolia differ from their colder homologues by annual and monthly temperatures; western associations were separated from eastern ones in terms of annual and seasonal precipitation gradients. Discriminant analysis was a good technique to explore climatic gradients not shown by other general ordination or classification methods.
Keywords: Bioclimatic indices; climate; Continentality; Discriminant analysis; Summer aridity; Water availability

Eastern Mediterranean Quaternary paleoclimates from pollen and isotope records of marine cores in the Nile Cone Area - Cheddadi, Rachid; Rossignol-Strick, M (Paleoceanography, 1995)
Pollen spectra from three eastern Mediterranean cores have been used to document the paleoclimates of the Levantine Basin borderlands over the last 250 kyr to establish the relationship between this regional climate data set and the global climate as recorded by foraminiferal δ18O and to compare it with proximal land pollen records. Core MD 84 642 with eight sapropels covers the last two climatic cycles up to the early Holocene, MD 84 627 with four sapropels goes back to 125 kyr, and MD 84 629 with one sapropel covers the last 70 kyr. The sedimentation rate decreases from core 629, located at the shallowest depth beneath the Nile River plume, to cores 627 and 642. During the interglacials defined by a low 18O/16O ratio, the abundance of tree pollen is maximum and points to an optimum Mediterranean climate with greatest humidity, including some summer rainfall. During glacial maxima, with highest 18O/16O ratio, the pollen abundance is high for steppe and semidesert plants and low for trees, indicating a definitely more arid, more continental, and probably colder climate. The variations of pollen abundance occur in phase with those of the foraminifer δ18O record. This signifies that the regional climate of the Levantine Basin borderlands had the same temporal pattern as the global ice volume documented by the ice volume curve.
Keywords: climate; Eastern Mediterranean; Evergreen and deciduous forests; isotopic stratigraphy (voyant); pollen spectra

Geographical variation in the density of the white stork Ciconia ciconia in Spain: Influence of habitat structure and climate - Carrascal, L. M.; Bautista, L. M.; Lázaro, E. (Biological Conservation, 1993)
The spatial variation in the density of white storks Ciconia ciconia in Spain is analysed with respect to landscape and meteorological variables. The density of breeding pairs in 1985 was negatively correlated with surface cover of woodlands and shrublands, and posi- tively correlated with the area of dry or wet grasslands, reflecting .food availability and foraging preferences of the storks. Average minimum temperature in April-May (the first .few days after hatching) was also negatively correlated with stork density, and the reproductive success in a colony at El Tietar (Avila) was inversely correlated with the number of days with precipitation in May. The negative influence of minimum temperature and precipitation on breeding density appears to be linked with the mortality of recently born nestlings. Practical recommendations are made for the conserva- tion of the Spanish population of white storks through incentive use of pastures, meadows and 'dehesas' for cattle grazing. Reintroduction efforts must be direct towards zones having large areas of these habitats, and mild weather
Keywords: climate; distribution; habitat; Spain; white stork

Geographical variation in the density of the white stork Ciconia ciconia in Spain: Influence of habitat structure and climate - Carrascal, L M; Bautista, L M; Lázaro, E (Biological Conservation, 1993)
The spatial variation in the density of white storks Ciconia ciconia in Spain is analysed with respect to landscape and meteorological variables. The density of breeding pairs in 1985 was negatively correlated with surface cover of woodlands and shrublands, and posi- tively correlated with the area of dry or wet grasslands, reflecting .food availability and foraging preferences of the storks. Average minimum temperature in April-May (the first .few days after hatching) was also negatively correlated with stork density, and the reproductive success in a colony at El Tietar (Avila) was inversely correlated with the number of days with precipitation in May. The negative influence of minimum temperature and precipitation on breeding density appears to be linked with the mortality of recently born nestlings. Practical recommendations are made for the conserva- tion of the Spanish population of white storks through incentive use of pastures, meadows and 'dehesas' for cattle grazing. Reintroduction efforts must be direct towards zones having large areas of these habitats, and mild weather
Keywords: climate; distribution; habitat; Spain; white stork

DYNAMIC STAGES IN EXTRAZONAL COENOSIS OF QUERCUS-ILEX IN ABRUZZO (CENTRAL ITALY) - CORBETTA, F; PIRONE, G (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
This note has as its objective the study of extrazonal communities of Quercus ilex, found in the inner valleys of Abruzzo (Central Italy) and of the coenosis of substitution dynamically linked to them: Some valleys in the mountains of Abruzzo, and particularly those at Sulmona and Capestrano, to which this research refers, represent, from a climatic point of view, small bounded areas which are thermically high and which interrupt the continuity of the line of low temperatures which characterize the ridge of the Apennines. Other features of these inner areas (whose bottom is about 300–400 m) are the high annual temperature range of about 18°–20°C, and the quite low rate of rainfall (often below 700mm; below 500mm at Capestrano) because of the mountains which stop the wet winds.
Keywords: APS; climate; extrazonal comunities; Italy; Quercus ilex